How precious is the reliability of the residential electricity service in developing economies? Evidence from India - Pradeep Perera; Tapan Sarker; K. M. Nazmul Islam; Fateh Belaïd; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2021)
This paper aims to examine the challenges of expanding access to an affordable electricity supply for rural households by addressing the subsidies and cost recovery of the existing tariff policy in the context of Uttar Pradesh (UP), India. The study used household survey data to assess the consumer attitudes, level of satisfaction, and affordability of electricity in rural areas of UP, where more than 78% of the state's population resides. Further, it examined the regulatory challenges of expanding access to the electricity supply to rural households in an affordable and fiscally sustainable manner. The main conclusions are that households have a higher level of satisfaction and willingness to pay as the supply duration has increased from 12-13 hours per day before 2017 to 15-18 hours per day. By contrast, the affordability of the lifeline level of consumption for people belonging to lower-income groups is low, and there is a need for continued fiscal subsidies to make the electricity affordable for this group of consumers. The case highlights that the prevailing electricity market, based on unmetered connections, a fixed monthly tariff, and a subsidy policy of fiscal transfers to the utility, is suboptimal in its targeting efficiency, incentives for energy conservation, and transparency of subsidy payments. The policy recommendations that this paper provides apply to developing countries that are reforming their electricity markets.
Keywords: O12; O13; O53; Q41; 330; affordability; access to electricity; regulatory framework; fiscal sustainability; India; Elektrizitätsversorgung; Subvention; Kostendeckung; Ländlicher Raum; Privater Haushalt; Befragung; Uttar Pradesh; Indien